Odor representations of the city. Olfactory experiences in literature: a sociological reading (REVISTA NODO, 2020)
This article is part of the classic and contemporary approaches to the sociology of the senses, as well as the interest in the relation between the city and smells. Research on odor has gone to various literary references ((Howes, Classen y Synnott, 1994, p. 4; Synnott, 2003, p. 446; Drobnick, 2006; Porteous, 2006; Waskul, Vannini y Wilson, 2009; Solander, 2010; Verbeek y Campen, 2013; Low, 2013, p. 292; Rindisbacher, 2015; Jaquet; 2016, p. 168) as significant references that allow us to enunciate some problematizations associated with socio-historical and cultural research on odors.The reference to the oeuvre of male writers is remarkable, while the allusion to female writers is underrepresented. The objective of this article is to present how the smells in the city are represented (Lahire, 2006; Becker, 2015) by two contemporary Mexican writers: Guadalupe Nettel (1973) and Ana Clavel (1961). Specifically, I am interested in showing how specific meanings attributed to unpleasant olfactory experiences are narrated in the city. The intention is to make visible other voices with a heuristic performance for the sociological investigation of odors, gender, and their relationship with human and non-human entities in large cities.
Keywords: cities; smells; gender; literature; sociology